2019
DOI: 10.12968/jowc.2019.28.4.198
|View full text |Cite
|
Sign up to set email alerts
|

Management of purpura fulminans skin lesions in a premature neonate with sepsis: a case study

Abstract: Purpura fulminans is a severe and rapidly progressive septic process characterised by the development of haemorrhagic and ecchymotic lesions and skin necrosis. It can appear on any part of the body but predominantly affects the limbs. Purpura fulminans is a rare but possible complication in paediatric patients, especially neonates. It can increase their risk of morbidity and mortality if not treated early and cause a severe long-term condition in survivors of the infectious episode, including amputation. For p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…If the measurement data in the study conforms to the normal distribution, it is presented in the form of mean ± standard deviation false(truexthinmathspace±s), and the falset test is used for inter group comparison. [14] If not, it uses falseM(P25P75) for representation and Mann Whitney U test for Mann–Whitney U testthe 2 groups; Friedman test is used for skewed distribution data related to multiple groups; Pairwise comparison uses Wilcoxon signed rank sum test. [15] The counting data is expressed in frequency or percentage form, and falseχ2 test is utilized for inter group comparison.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…If the measurement data in the study conforms to the normal distribution, it is presented in the form of mean ± standard deviation false(truexthinmathspace±s), and the falset test is used for inter group comparison. [14] If not, it uses falseM(P25P75) for representation and Mann Whitney U test for Mann–Whitney U testthe 2 groups; Friedman test is used for skewed distribution data related to multiple groups; Pairwise comparison uses Wilcoxon signed rank sum test. [15] The counting data is expressed in frequency or percentage form, and falseχ2 test is utilized for inter group comparison.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…33,34 Hyperoxygenated fatty acids have been noted to aid in more rapid wound healing in infants with PF. 35 Fresh frozen plasma is one method to replace missing factors, but it contains little protein C. 36 Outcomes with recombinant human activated protein C (drotrecogin alfa) are mixed, and studies have shown no benefit in reducing the risk for death. 37,38 Protein C concentrate has shown therapeutic benefit in some case reports and small retrospective studies.…”
Section: A B Cmentioning
confidence: 99%
“…One of the alternatives to these compounds is olive oil which is more accessible and more affordable than HOFA. [ 12 18 ] Olive oil is one of the medicinal plants that, due to its uncomplicated and many healing properties, has attracted the attention of many researchers. [ 8 11 ] Olive oil is rich in essential fatty acids oleic acid, linoleic acid, phytosterol, and squalene, which increase hydration, skin protection, and skin regeneration.…”
Section: Introductionmentioning
confidence: 99%